Penerapan Pengaturan Victim Impact Statement Pada Perkara Tindak Pidana Lingkungan Hidup Dalam Memenuhi Perlindungan Korban (RechtJiva, 2025)
This research examines the urgent need for regulating Victim Impact Statements (VIS) in environmental criminal cases in Indonesia with a focus on enhancing victims' legal protection and participation. Despite existing environmental laws, enforcement remains suboptimal, and victims often lack sufficient protection, typically limited to witness status. VIS provides victims the opportunity to express the impact they have suffered, a practice already implemented in countries like the United States. This study addresses two key questions: (1) Why is it urgent to regulate VIS in environmental criminal cases? and (2) How should VIS regulation be formulated? Using a normative juridical method, the research employs legislative, comparative, and analytical approaches, analyzing primary, secondary, and tertiary legal materials. The findings highlight that regulating VIS is essential to ensure procedural justice for victims, align with the right to a healthy environment, and address the growing environmental damage globally. The comparative analysis of the U.S. framework offers insights for Indonesia to develop a tailored VIS regulation consistent with its legal system.